2021
DOI: 10.1515/jiip-2020-0140
|View full text |Cite
|
Sign up to set email alerts
|

Inverse problem of Mueller polarimetry for metrological applications

Abstract: Inverse problem of Mueller polarimetry is defined as a determination of geometrical features of the metrological structures (i.e. 1D diffraction gratings) from its experimental Mueller polarimetric signature. This nonlinear problem was considered as an optimization problem in a multi-parametric space using the least square criterion and the Levenberg–Marquardt algorithm. We demonstrated that solving optimization problem with the experimental Mueller matrix spectra taken in conical diffraction configuration hel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…This has been verified and shown that in any other measurement configuration the different sources of the non-zero off-diagonal elements mix, making it more difficult to identify the profile asymmetry, and the sensitivity may disappear at azimuth 0 deg 19 23 …”
Section: Symmetry Relations To Consider In Mueller Matrix Measurementsmentioning
confidence: 88%
See 2 more Smart Citations
“…This has been verified and shown that in any other measurement configuration the different sources of the non-zero off-diagonal elements mix, making it more difficult to identify the profile asymmetry, and the sensitivity may disappear at azimuth 0 deg 19 23 …”
Section: Symmetry Relations To Consider In Mueller Matrix Measurementsmentioning
confidence: 88%
“…This has been verified and shown that in any other measurement configuration the different sources of the non-zero off-diagonal elements mix, making it more difficult to identify the profile asymmetry, and the sensitivity may disappear at azimuth 0 deg. [19][20][21][22][23] As a consequence, special attention is required for the precise alignment of the sample before measurement, as any deviation from φ ¼ 90 deg leads to off-diagonal responses itself, which can be misleading. Using an ellipsometry tool with a precise rotation stage, the following test can be performed to identify the source of the MM off-diagonal response.…”
Section: Simulation Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…With the cost function defined as Equation ( 19), the system parameter p sys could be obtained from the measured light intensity I meas by using the Levenberg-Marquardt algorithm [35].…”
Section: Calibration Of the Waveplate Retardance Fluctuationmentioning
confidence: 99%
“…Thus, by measuring these modulations or loss of polarization, we may deduce the polarimetric properties (e. g. diattenuation, birefringence, depolarization [7]) of a sample and use them for its characterization. This approach was widely explored in metrological applications [8,9], food quality control [10][11][12], pharmaceutical drug studies [13,14], biomedical diagnosis [15][16][17][18][19][20], etc. Using changes in tissue depolarization with pathology development for histology analysis and diagnosis was extensively studied in [21][22][23][24][25] for different types of tissue.…”
Section: Introductionmentioning
confidence: 99%